From Halo Effective Field Theory to the study of breakup and transfer reactions: reliably probing the halo structure of 11Be and 15C. (September 2020) - Moschini, L; Yang, J; Capel, P
Abstract: In this work we study one-neutron halo nuclei, and in particular 11 Be and 15 C, which can be seen as an inert core of 10 Be or 14 C plus a loosely bound neutron. During the last decades several transfer and breakup reactions involving these systems have been measured on different targets and energies. We study these processes using one single structure model for each nucleus applying the halo effective field theory (Halo EFT) at next-to-leading order NLO. The main parameters of this EFT are adjusted on nuclear-structure data and/or ab initio predictions. We model the transfer reaction within the Adiabatic Distorted Wave Approximation (ADWA) and the breakup process applying an eikonal model with a consistent treatment of nuclear and Coulomb interactions at all orders. At high energy, our model includes a proper treatment of special relativity Our theoretical calculations are in good agreement with experiment for a variety of reaction observables, thus assessing the robustness of the structure model provided for these nuclei. This new idea enables us also to reliably estimate the nuclear-structure observables that actually affect the reaction process, and hence that can be inferred from such measurements.